Application of weighted gene co-expression network and immune infiltration for explorations of key genes in the brain of elderly COVID-19 patients - Huang, Lixia; Qin, Wei; Guo, Zirui; Li, Xiaoyu; Li, Fajiu; Wang, Xiang (Frontiers in Immunology, 2023)
Introduction Although many studies have demonstrated the existing neurological symptoms in COVID-19 patients, the mechanisms are not clear until now. This study aimed to figure out the critical molecular and immune infiltration situations in the brain of elderly COVID-19 patients. Methods GSE188847 was used for the differential analysis, WGCNA, and immune infiltration analysis. We also performed GO, KEGG, GSEA, and GSVA for the enrich analysis. Results 266 DEGs, obtained from the brain samples of COVID-19 and non-COVID-19 patients whose ages were over 70 years old, were identified. GO and KEGG analysis revealed the enrichment in synapse and neuroactive ligand-receptor interaction in COVID-19 patients. Further analysis found that asthma and immune system signal pathways were significant changes based on GSEA and GSVA. Immune infiltration analysis demonstrated the imbalance of CD8+ T cells, neutrophils, and HLA. The MEpurple module genes were the most significantly different relative to COVID-19. Finally, RPS29, S100A10, and TIMP1 were the critical genes attributed to the progress of brain damage. Conclusion RPS29, S100A10, and TIMP1 were the critical genes in the brain pathology of COVID-19 in elderly patients. Our research has revealed a new mechanism and a potential therapeutic target.